2022
DOI: 10.3390/ma15155253
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous-Based Synthesis of Photocatalytic Copper Sulfide Using Sulfur Waste as Sulfurizing Agent

Abstract: Most of the copper sulfide synthetic approaches developed until now are still facing issues in their procedure, such as long synthesis duration, high energetic consumption, and high implementation costs. This publication reports a facile and sustainable approach for synthesizing copper sulfides on a large scale. In particular, an industrial by-product of sulfur waste was used as a sulfurizing agent for copper sulfide synthesis in a water medium. The reaction was performed in the hydrothermal environment by fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…On the other hand, when reference and waste photocatalysts are embedded in films, the degradation rate reaches a value 1.4 times higher with CuS particles obtained from waste (CuSw/Fi sample – 0.5203 min −1 ; CuSr/Fi – 0.3834 min −1 ) (Figure 2C,D). It is known from previous work [ 35 ] that CuSw has a larger crystallite average size than CuSr (39 and 35 nm, respectively), which can result in a higher degradation rate as reported by Goktas et al. [ 36 ] in their work on ZnO.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…On the other hand, when reference and waste photocatalysts are embedded in films, the degradation rate reaches a value 1.4 times higher with CuS particles obtained from waste (CuSw/Fi sample – 0.5203 min −1 ; CuSr/Fi – 0.3834 min −1 ) (Figure 2C,D). It is known from previous work [ 35 ] that CuSw has a larger crystallite average size than CuSr (39 and 35 nm, respectively), which can result in a higher degradation rate as reported by Goktas et al. [ 36 ] in their work on ZnO.…”
Section: Resultsmentioning
confidence: 95%
“…The added CuS is synthesized by using industrial sulfur waste as a sulfuring agent, according to the method previously reported. [ 35 ] In order to validate the applicability as a waste‐based photocatalyst (CuSw), we have also synthesized a reference sample of CuS by using pure sulfur, as a standard sulfurizing agent (CuSr, reference sample). The photocatalytic activity in the degradation of TC (50 mg L −1 ) of both photocatalysts has been tested.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations